Presence of Borrelia burgdorferi and rickettsial pathogens in Rhipicephalus sanguineus ticks of Monterrey, city of Northeastern of Mexico - Tamez González, Roberto; Almaza Ferrer, Ana; Torres, Javier; Gordillo Pérez, María Guadalupe (2018)
Rhipicephalus sp is endemic throughout the world, it has capacity of host and transmit pathogens to the dogs and keep enzootic cycle of R. rickettsi and Ehrlichia canis (E. canis), causal agent spotted fever from the rocky mountain spotted fever and the canine Ehrlichiosis respectively. Emergent tick borne disease was reported in Mexico recently, but the domestic cycle has been not studied.